Now what? The experience of youth leaving care in four European countries - Roxana Ungureanu; Mihaela Tomita (Technium Social Sciences Journal, 2020)
This paper draws on evidence from an Erasmus+ funded project, Now What?: Preparing and Empowering Youth Leaving Care, which aimed to find out the development of an integrated approach that will successfully achieve the provision of guidance on effective education, work and living in the community and support and help when the youth face crises that are an inevitable part of their transition to adulthood and independence. The research was carried out over two years by a consortium of four countries: Romania, Greece, Albania and Portugal. The principal method used was a biographical narrative interviews with a sample of 390 young people aged 15–20. Positive results came from a range of different interventions, e.g. mentoring projects and structured individualized support. We conclude that most focused interventions seem to improve foster children’s poor academic achievements, but mentoring projects have so far the best empirical support from evaluations with rigorous designs. Also there’s a definite need for more intervention research.